Protective mechanisms of adenosine 5′-monophosphate in platelet activation and thrombus formation - Fuentes, Eduardo; Badimon, Lina; Caballero, Julio; Padró, Teresa; Vilahur, Gemma; Alarcón, Marcelo; Pérez, Pablo; Palomo, Iván (Thrombosis and Haemostasis, 2014)
Platelet activation is relevant to a variety of acute thrombotic events. We sought to examine adenosine 5′-monophosphate (AMP) mechanisms of action in preventing platelet activation, thrombus formation and platelet-related inflammatory response. We assessed the effect of AMP on 1) P-selectin expression and GPIIb/IIIa activation by flow cytometry; 2) Platelet aggregation and ATP secretion induced by ADP, collagen, TRAP-6, convulxin and thrombin; 3) Platelet rolling and firm adhesion, and platelet-leukocyte interactions under flow-controlled conditions; and, 4) Platelet cAMP levels, sP-selectin, sCD40L, IL-1β, TGF-β1 and CCL5 release, PDE3A activity and PKA phosphorylation. The effect of AMP on in vivo thrombus formation was also evaluated in a murine model. The AMP docking with respect to A2 adenosine receptor was determined by homology. AMP concentration-dependently (0.1 to 3 mmol/l) inhibited P-selectin expression and GPIIb/IIIa activation, platelet secretion and aggregation induced by ADP, collagen, TRAP-6 and convulxin, and diminished platelet rolling and firm adhesion. Furthermore, AMP induced a marked increase in the rolling speed of leukocytes retained on the platelet surface. At these concentrations AMP significantly decreased inflammatory mediator from platelet, increased intraplatelet cAMP levels and inhibited PDE3A activity. Interestingly, SQ22536, ZM241385 and SCH58261 attenuated the antiplatelet effect of AMP. Docking experiments revealed that AMP had the same orientation that adenosine inside the A2 adenosine receptor binding pocket. These in vitro antithrombotic properties were further supported in an in vivo model of thrombosis. Considering the successful use of combined antiplatelet therapy, AMP may be further developed as a novel antiplatelet agent.
Keywords: Platelets; antithrombotic; adenosine 5′-monophosphate; PDE inhibition; A2A receptor